Pengetahuan Masyarakat tentang Suplemen Minuman Berenergi terhadap Risiko Penyakit Ginjal Kronik di Kelurahan Simpang Baru Kecamatan Tampan Pekanbaru - Yolanda Fandra; septi muharni; ratna sari dewi (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2019)
Energy drink supplement is a health product that contains one or more substances that are nutritional (vitamins, minerals and amino acids) or drugs. This study aims to look at public knowledge about the use of energy drink supplements for the risk of chronic kidney disease in Simpang Baru district, Tampan District, Pekanbaru city. This research is an observational / survey research which is descriptive in nature. Sampling was done by purposive sampling, samples obtained in this study were 100 respondents who used energy drink supplements at least once a week. The results showed that community knowledge in the Simpang Baru sub-district was included in the sufficient category (64.83%) with the division of categories of knowledge about the definition of a supplement with enough energy drinks (62%), the content of the supplement with enough energy drinks (65.66%), the purpose / reason consume adequate energy drink supplements (75%), effects / risks after taking adequate energy drink supplements (69.6%) and when consuming energy drink supplement people in the Simpang Baru sub-district community have less knowledge level (52.33%). From these results it can be concluded that public knowledge about the use of energy drink supplements in Simpang Baru village, Tampan sub-district, Pekanbaru city is included in the sufficient category (64.83%).